FACTORS AFFECTING THE QUALITY OF LIFE OF PATIENT DIAGNOSIS WITH BREAST CANCER PATIENTS: A CROSS-SECTIONAL STUDY.: JPUMHS;2024:14:04,185-195. http://doi.org/10.46536/jpumhs/2024/14.04.578 - Amir Sultan1, Zobia Perveen2, Saleem Ullah3, Syed Aamer Hussain4, Noshaba faiz5 Shamaila Ayub6, Samina Rani7 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: The objective of the study was to identify the quality of life and associated factors. METHODOLOGY: The study was conducted in the two tertiary care hospitals of Khyber pukhtankhwa Pakistan from April to July 2024 using analytical cross- sectional study design, and the study participants were the patient diagnosed with breast cancer and completed treatment of chemotherapy or surgery and continuous their followup in out-patient department. The sample size of the study was 170, while sampling technique was convenient. The data was collected through valid and reliable questionnaire. The data was analyzed through SPSS 24 as descriptive and inferential statistics. RESULTS: The overall quality of life of the study participants was average having means score of 2.4 ± 0.19. In domains high mean score belong to physical P-WB 2.9 ± 0.36, then emotional E-WB 2.8 ± 0.41, and social S-WB was 2.5 ± 0.26, while the minimum mean score belongs to F-WB F- WB 1.38 ± 0.37. Age group 50 and above mean score, married, no education, housewives, diabetic mellitus, stage 3 cancer, low monthly income, and patient having surgery well-being of the majority of the domains were perform better than their comparing categories. CONCLUSION: The study concluded that the QOL of patient diagnosed with BC is affected, but moreover the F-WB of the patient is more affected more. The socio- demographic characteristics such as age, marital status, stages of cancer and treatment is closely linked and associated with QOL